An Investigation of Assimilation and Contrast Effects in Backward Evaluative Conditioning - Green, Luke John Stanley (Curtin University, 2020)
Evaluative conditioning (EC) refers to the acquisition of likes and dislikes. During backward EC, a neutral conditional stimulus (CS) presented after a valenced unconditional stimulus (US) can acquire the same or opposite valence to the US. Relational instructions, affective relief or disappointment, and US onset predictability determined the direction of backward EC, while US intensity and offset predictability had no effect. The backward conditioning paradigms employed revealed novel insights regarding CS valence acquisition and measurement.